Foreign Direct Investment in Defence Sector in India : Problems and Prospects - Mahajan, Dinesh (Journal of Commerce and Trade, 2016)
India is surrounded by hostile neighbourers. The need for defence of its borders has been on priority since independence. For this purpose defence production has to be upgraded to make it at par with the military power of other countries. A humble attempt has been made to exhibit the trends of FDI inflows in the defence sector and to examine the problems of FDI inflows in this sector in India. The prospects for FDI inflows in defence sector have also been highlighted. The time period covered herein ranges from 2001 to 2015 (upto September). The study reveals that FDI inflows in this sector have fluctuated from Rs. 2.36 millions in the year 2000-2005 to Rs. 4.80 millions in the year 2015 (upto September). The major problems in FDI inflows in this sector are the perception of viability, selection of private partner, insufficient FDI limit, safety of intellectual property rights, technology, availability of finance and quality of work force. The prospects for FDI in this sector are joint ventures, likely manufacturing hub, fighter aircrafts and helicopters, cost-effective manpower, government policy of reducing imports, increase in defence expenditure and submarines and naval vessels.